2017
DOI: 10.1111/ele.12818
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall variability and fine‐scale life history tradeoffs help drive niche partitioning in a desert annual plant community

Abstract: Tradeoffs have long been an essential part of the canon explaining the maintenance of species diversity. Despite the intuitive appeal of the idea that no species can be a master of all trades, there has been a scarcity of linked demographic and physiological evidence to support the role of resource use tradeoffs in natural systems. Using five species of Chihuahuan desert summer annual plants, I show that demographic tradeoffs driven by short-term soil moisture variation act as a mechanism to allow multiple spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Little is known of the photosynthetic physiology of these species, although there appear to be trade‐offs between resource acquisition and drought for E. glaucus (Balachowski & Volaire, ). Some life history trade‐offs might appear minor but cause important interactions with drought (Shriver, ). Moreover, we used potted, watered, fertilized plants, so they were presumably not affected by competition for light, water, or nutrients as would be plants rooted in the soil of plots.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known of the photosynthetic physiology of these species, although there appear to be trade‐offs between resource acquisition and drought for E. glaucus (Balachowski & Volaire, ). Some life history trade‐offs might appear minor but cause important interactions with drought (Shriver, ). Moreover, we used potted, watered, fertilized plants, so they were presumably not affected by competition for light, water, or nutrients as would be plants rooted in the soil of plots.…”
Section: Discussionmentioning
confidence: 99%
“…Partitioning of available resources can mediate community responses to drought stress and is affected by the specific plant community composition at the time of drought and by the amount of diversity of the system (Reich, ; Felton et al ., ). Demographic tradeoffs in growth and survival can promote niche partitioning and the distribution of limiting resources during a drought (Shriver, ).…”
Section: Site‐specific Characteristics Influencing Community Resistanmentioning
confidence: 99%
“…The need to understand and anticipate ecological responses to climate change has led to a growing literature linking climate conditions to demographic rates and population dynamics. This work has expanded our knowledge of how plant demographic rates respond to changes in environmental conditions through time (Dalgleish et al 2011, Chu et al 2016, Shriver 2016, 2017, Tomasek et al 2019) and across large spatial gradients (Angert 2006, Eckhart et al 2011, Gelfand et al 2013, Merow et al 2014). For example, Dalgleish et al (2011) identified winter and summer climate conditions as important for explaining inter‐annual variation in demographic rates of steppe plants.…”
Section: Introductionmentioning
confidence: 98%